Morphological and mechanical properties of drawn poly(l‐lactide) electrospun twisted yarns. Issue 7 (26th July 2017) - Maleki, Homa; Barani, Hossein
Abstract : In this study, the continuous twisted PLLA yarns were produced using an electrospinning device consists of two oppositely charged nozzles. The electrospinning process was performed at different twist rates. The electrospun twisted yarns were drawn at different extension ratios of 50% and 100% and their morphological and mechanical properties of post‐drawn yarns were investigated. The morphological studies at all twist rates shown that uniform and smooth fibers without any bead were formed. Increasing the twist rate up to 240 rpm resulted to a decrease in the average diameter of the fibers in the yarn structure. After uniaxially drawing of the yarns, the average diameter of fibers and thus the yarn diameter decreased. The post‐drawing process enhanced the crystallinity of the fibers in the yarn structure. Furthermore, by increasing the extension ratio, the tensile strength and modulus of yarns increased, while the elongation at break (%) decreased. POLYM. ENG. SCI., 58:1091–1096, 2018. © 2017 Society of Plastics Engineers